THE EFFECT OF DISCIPLINE AND HUMAN RESOURCES COMPETENCE ON EMPLOYEE PERFORMANCE OF BADAN PENGUSAHAAN (BP) BATAM - Timbul Dompak; Angel Purwanti (Universitas Putera Batam, 2022)
This study was aimed at analyzing the effect of discipline (X1) and human resource competence (X2) on the employee performance of Badan Pengusahaan (BP) Batam (Y). The approach in this study uses quantitative methods, by distributing questionnaires to respondents. The research sample is 100 people. The results show that (1) partially there is an effect of discipline on employee performance with a t-count value (4,163) > t-table (1,984), (2) partially there is an effect of human resource competence on employee performance with a t-count value (5.519) > t-table (1.984), (3) simultaneously there is the influence of discipline and competence of human resources on employee performance with the value of F-count (39.247) > F-table (3.09).